THE INFLUENCE OF PHYTOTHERAPY ON PROLACTIN LEVEL IN MACROPROLACTINOMA PATIENTS - TrogrliÄ‡, Ivo; TrogrliÄ‡, Dragan; TrogrliÄ‡, Zoran (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
The study aims at demonstrating the efficiency of phytotherapy in regulation of prolactin levels in patients diagnosed with pituitary macroprolactinoma. The study made use of workup outcomes submitted by treating healthcare facilities where the patients were first diagnosed with macroprolactinomas based on diagnostic imaging (MRI and/or CT), laboratory workup, and hormone status estimation. The data in reference served as the baseline for a comparative follow-up of phytotherapeutic efficiency in terms of comparison of medical data obtained prior to phytotherapy and those submitted following herbal remedy use. The study displays the results of a five-year follow-up of macroprolactinoma patients undergoing phytotherapy. In well-responding patients, the benefit of phytotherapy in terms of prolactin level putdown can be seen 3-5 months following the phytotherapy commencement. A special attention should be paid to the favourable results obtained with patients who chose to resort to phytotherapy only. The primary outcome measure used to monitor the efficiency of the administered phytotherapy was prolactin level determined prior to, during the course of, and following phytotherapy. Implementation of phytotherapy to the effect of prolactin level regulation in patients diagnosed with macroprolactinoma, represents a completely novel therapeutic approach. The majority of the diseased resorted to phytotherapy once they were left out of any other therapeutic option offered by their treating healthcare facilities. This fact gives a substantial rise to the significance of the results presented herein and justifies the role of phytotherapy in macroprolactinoma-induced hyperprolactinaemia treatment.